2011
DOI: 10.1016/j.neuroscience.2011.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of histamine H3 receptor inverse agonist thioperamide, given alone or in combination with the N-methyl-d-aspartate receptor antagonist dizocilpine, on reconsolidation and consolidation of a contextual fear memory in mice

Abstract: Abstract-Albeit there is no doubt that histamine and its H 3 receptors participate in several aspects of learning and memory, such as memory consolidation, nothing is known about their potential involvement in memory reconsolidation. On the basis of previous reports of pro-cognitive effects of histamine H 3 receptor inverse agonists (which augment histamine release), we investigated to what extent the most representative of them, thioperamide, is able to facilitate reconsolidation of a contextually-conditioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 70 publications
8
16
1
Order By: Relevance
“…Therefore, while context reexposure led to behaviorally defined extinction for all durations, this extinction was apparently NMDA receptor-dependent only for the 30-min condition. Moreover, the reconsolidation impairment with the brief reexposure duration was observed in spite of a significant between-session decline in freezing, as has been previously documented in the literature (Charlier and Tirelli 2011;Brabant et al 2013;Heath et al 2015). Importantly, we observed a similar pattern of freezing reduction even in the animals that received MK-801 after context reexposure, no matter how long the session lasted for (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, while context reexposure led to behaviorally defined extinction for all durations, this extinction was apparently NMDA receptor-dependent only for the 30-min condition. Moreover, the reconsolidation impairment with the brief reexposure duration was observed in spite of a significant between-session decline in freezing, as has been previously documented in the literature (Charlier and Tirelli 2011;Brabant et al 2013;Heath et al 2015). Importantly, we observed a similar pattern of freezing reduction even in the animals that received MK-801 after context reexposure, no matter how long the session lasted for (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The role of histamine transmission is practically unknown in reconsolidation processes. In our laboratory, we have previously demonstrated that thioperamide can block the deficit in reconsolidation produced by dizocilpine in the fear conditioning test [14].…”
Section: Introductionmentioning
confidence: 99%
“…During the consolidation phase, memories are susceptible to disruption when amnesic treatments are applied shortly after learning such as electroconvulsive shocks [13]. Glutamate transmission and in particular N-methyld-aspartate (NMDA) receptors play a critical role in consolidation of fear memories since the blockade of NMDA receptors impairs memory consolidation [14] whereas NMDA receptor activation facilitates consolidation [15]. In addition, other neurotransmitter systems like histamine can facilitate the consolidation of memories [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations